Gaetano Donizetti by Franz Liszt, the piano in the service of the opera - Krzywoszyński, Przemysław (Interdisciplinary Studies in Musicology, 2018)
The aim of the paper is to analyze Franz Liszt's piano interpretations that constitute excellent operatic transcriptions and reminiscences from the operas of Gaetano Donizetti. There are seven piano works based on six of Donizetti’s operas, among them bar-for-bar transcriptions of particular fragments as well as masterly syntheses of many musical themes. We try to argue that Donizetti was an inspiration for Liszt and that the Hungarian composer was not only an eminent connoisseur and admirer of bel canto, but also made an important contribution to the rediscovery of Italian opera. These transcriptions are an excellent example of a sincere tribute from one great composer to another; they highlight some of the treasures among Donizetti’s compositions, as well as the talent of the author of the transcriptions.